Anaksymander i Anaksymenes z Miletu – ważniejsza doksografia i fragmenty - Wesoły, Marian Andrzej (Peitho. Examina Antiqua, 2025)
In addition to the existing source editions and translations, several new works on the so-called Presocratics (i.e., early Greek philosophers) have been published (see bibliography). While this study continues our work on the translation of the doxography and fragments of these authors, this paper presents Anaximander and Anaximenes of Miletus, who dealt with the same issues of principles, cosmogony, astronomy, and meteorology. We deal with them separately, but in a similar arrangement of sources, slightly different from previous editions, taking into account as instructive the longest of all testimonies about Anaximander and Anaximenes, namely the accounts of Hippolytus of Rome in Refutatio omnium haeresium I 6–7. As previously with Thales, we approach these Milesians in a selective and systematic arrangement of testimonies and those few fragments which, although considered inauthentic by many researchers, we find extremely interesting, rather reliable, and worth quoting. For greater clarity, we have introduced appropriate thematic headings in our translation of these texts, which is as close to the original as possible. The brief information below may serve as an introduction to a new reading of the sources on Anaximander and Anaximenes of Miletus.